Finite Element Simulation Analysis of Dynamic Contact Characteristic of Deep Groove Ball Bearing - Bai Guicai; Shentu Liufang (Jixie chuandong)
A multi-body dynamic contact finite element model of a deep groove ball bearings that be used in planetary gear is established in LS-DYNA,based on explicit dynamics finite element method,considering effect of rotational speed of bearing outer ring,radial load and rotational speed of carrier,the simulation analysis of dynamic contact characteristic（displacement,velocity,stress and contact force）under different working conditions are carried out,the dynamic contact response of the bearing is obtained.The study shows that the rolling exist revolution and rotation movement during operation,the maximum and the minimum line speed occurred at the contact point with the outer ring and the inner ring.The maximum stress occurred when the rolling contact with outer ring or inner ring,and the influence of the rotational speed to the maximum stress is little.It is proved reliable based on the simulation results compared with Hertz solution.The contacting force fluctuation between the rolling and cage is bigger than that and the inner or outer ring,but the value is the minimum,the contacting force value between the rolling and the outer ring or inner is almost same with the radial load.